Chronic mast cell leukemia: a novel leukemia-variant with distinct morphological and clinical features - Valent, Peter; Reiter, Andreas (Leukemia research, 2015)
Mast cell leukemia (MCL) is a rare form of systemic mastocytosis characterized by leukemic expansion of mostly immature mast cells, organ damage, drug-resistance, and a poor prognosis. Even when treated with chemotherapy, most patients have a life-expectancy of less than one year. However, there are rare patients with MCL in whom the condition is less aggressive and does not cause organ damage within a short time. In these patients, mast cells exhibit a more mature morphology when compared to acute MCL. A recently proposed classification suggests that these cases are referred to as chronic MCL. In the present article, we discuss clinical, histopathological and morphological aspects of acute and chronic MCL.